Beruf(ung) DaF/DaZ Band 2 Festschrift zum 65. Geburtstag von Prof. Dr. Uwe Koreik - Gültekin-Karakoç, Nazan (Universitätsverlag Göttingen, 2022)
Prof. Dr. Uwe Koreik has played a decisive role in shaping the subject of German as a Foreign and Second Language in academic and institutional terms over the past decades. Under the title Beruf(ung) DaF/DaZ, which reflects Uwe Koreik's decades of commitment to the subject and the people associated with it, the commemorative publication for him on the occasion of his 65th birthday is now available. It combines 24 academic contributions and 16 vignettes in two volumes. The academic contributions, written by renowned representatives of the field, trace Uwe Koreik's academic career and address topics from his fields of work and research: Cultural Studies, Film and Literature, Places of Remembrance as well as the field of testing and examination. The vignettes from colleagues, companions and friends also take a look at the human side of Uwe Koreik in humorous and anecdotal form.